Linear Variable Differential Transformer Temperature Compensation Technique - Wandee Petchmaneelumka; Pitsini Mano; Vanchai Riewruja (My University, 2018)
A feedback technique to compensate for the temperature effect on the output signal of the linear variable differential transformer (LVDT) without losing the sensitivity is presented in this paper.The proposed technique is based on the use of a voltage-controlled amplifier to scale the amplitude of the excitation signal for temperature compensation.The proposed feedback technique provides the proportional-plus-integral control action to minimize the error caused by the temperature variation.The proportional-plus-integral action is realized using the integral scheme in the proposed technique.The peak amplitude of the LVDT output signal is sampled by the sample-and-hold circuit (SHC) to obtain the feedback and displacement signals, where the control signal of the SHC is provided by the LVDT output signal.The proposed LVDT temperature compensation technique is emphasized in terms of simple configuration and low cost.Note that the proposed technique is suitable for signal conditioners embedded in smart sensors and smart materials.The performance of the proposed technique is confirmed by experimental implementation using commercially available devices.The maximum error of the core displacement signal can be reduced from 6.52% for the uncompensated scheme to 0.098% for the compensated scheme at the ambient temperature of 70 °C.
Keywords: Differential protection; Analog and Mixed-Signal Circuit Design